PENGARUH KOMPETENSI KEPRIBADIAN DAN EFIKASI DIRI GURU TERHADAP KINERJA GURU YANG DIMEDIASI OLEH KOMITMEN ORGANISASIONAL ( Studi Pada Guru SMK Negeri Se Sub Rayon 01 Kota Semarang ) - Salimah, Salimah; Mindarti, Ceacilia Sri (Jurnal Ilmiah Telaah Manajemen, 2017)
This study aims to analyze the influence of personal competence, self-efficacy of teachers and teachers' organizational commitment to performance and the role of organizational commitment mediates the influence of personal competence and teachers self efficacy on performance of teachers on vocational high school teachers of Semarang’s rayon 01 on Semarang City.The population in this research is state and private vocational high school teachers of totaled 209 people. With Slovin method then the sample numbered 137 people. Then from 137 people, who returns the answer of the questionnaire amounted to 137 people.The results showed that (1) personal competence but not significant positive effect on organizational commitment, (2) self-efficacy of teachers is also positive but not significant effect on organizational commitment, (3) personal competence and a significant positive impact on teacher performance, (4) self-efficacy teacher positive and significant impact on teacher performance, (5) organizational commitment does not mediate the influence of personal competence on teachers performance, (6) organizational commitment does not mediate the influence of self - efficacy of teachers on teacher performance . Keywords : personal competence, self-efficacy of teachers, teachers' organizational commitment and performance.